Protection coordination study in bhutan transmission network - Gyeltshen, Thinley (My University, 2010)
Since the effects of an unreliable power system transmission can be widespread and affect millions of people, as well as damage to life and equipment, therefore one of the most important requirements of protection system is to isolate and disconnect faulted parts of the system selectively and quickly. This purpose can be achieved by proper coordination of protective devices. One of the aims of this thesis was to make a general guideline from which proper coordination of transmission system protection can be developed in Bhutan network. This thesis proposes a review of coordination of distance relays for transmission lines of a real network in Bhutan for study. The transmission network in Bhutan has under gone drastic change for past decade, due to growth of generation capacity with the target to generate 10,000MW by 2020 and target to achieve “Electricity for All by 2013”. It has become very much necessary to study and analyze the protection system of existing transmission network. This thesis also discusses the important of directional earth fault relay (67N) during the high impedance fault and its coordination. This thesis highlights the factor that effecting the operation of distance relay. This study is carried out using Computer Aided Protection Engineering (CAPE) software by Electrocon International Incorporated, Michigan, USA.
Keywords: Elkraftteknik; Electric power engineering